Biofilm Growth in Two Streams Draining Mountainous Permafrost Catchments in NE Greenland. Issue 3 (16th March 2020) - Pastor, A.; Wu, N.; Skovsholt, L. J.; Riis, T.
Abstract: The objective of this study was to evaluate how stream water nutrient concentrations influence biofilm accrual in streams draining mountainous permafrost headwaters. We selected six stream locations in the Zackenberg area (NE Greenland, 74°N) subjected to a gradient in the areal contribution of different geomorphological units in the watersheds and channel stability. We used nutrient diffusing substrates to evaluate biofilm growth (autotrophic and total biomass). We found elevated stream nitrate concentrations in samples from upstream reaches draining larger areas of solifluction sheets and bare rock and with higher channel instability. Nitrate had the highest standardized effect on autotrophic biofilm growth on control disks. However, stream biofilm growth was not nutrient limited as shown by the absence of an increase in biofilm biomass as a response to the experimental nutrient additions. The response to nutrient additions via diffusing substrates depended on the altitude gradient. Overall, our results showed stream nitrogen availability to be one of the main drivers of algal biofilm accrual in high‐Arctic streams, suggesting that the predicted changes in nutrient exports induced by climate change will have strong impacts on the biogeochemistry and ecological functioning of high‐Arctic streams. Plain Language Summary: Biofilms are complex aggregates of microbes that are responsible of major ecological functions in streams ecosystems, including primary production, nutrient cycling, and food and habitat provision. Despite of the high sensitivity of the Arctic to climate‐driven changes, there is still little information on how biofilms would respond to those, hampering our understanding on the ecological effects to freshwaters functioning and the impacts to downstream ecosystems. Here, we evaluate how nutrient concentrations in stream water influence biofilm accrual. We deployed artificial substrates amended with nutrients (nitrogen and phosphorous) in six streams draining mountainous permafrost headwaters in NE Greenland and measured biofilm accrual both the autotrophic fraction and total biomass. Our results showed stream nitrogen concentrations to be one of the main drivers. Thus, we suggest that the predicted changes in nutrient exports induced by climate change will have strong impacts on the biogeochemistry and ecological functioning of high‐Arctic streams. Key Points: High nitrate concentrations were found in two high‐Arctic headwater streams draining mountainous permafrost catchments during late summer Autotrophic biofilm growth, measured as chlorophyll a, was highly responsive to nitrate availability Stream biofilm growth responded to nutrient additions (via diffusing substrates) and the effect depended on the stream environmental gradient